Evaluation of a set of parameters for the optimum microencapsulation of chloroquine phosphate with ethylecellulose. (Journal of Science and Technology, 2016)
The effect of various formulation factors for the optimum encapsulation of chloroquine phosphate with ethylcellulose has been studied. The release of the drug from the microcapsules was dependent on the quantity of ethylcellulose employed, the quantity of drug used, the quantity of these substances in the isolated products and the ethylcellulose rejected during microencapsulation.